Patients deceased in Cienfuegos city. Kind of patients, causes and place where they died. - María Gloria Fabregat Rodríguez (Medisur)
Fundament: The analysis of mortality constitutes an important element for any study about the health situation of any population and for its epidemiological vigilance. Objective: to describe the behaviour of the first seven causes of death in the municipalities from Cienfuegos province according to age group and sex. Method: descriptive study about the behaviour of the first seven causes of death in Cienfuegos province from 1990-2002 according to age group and sex. The variables under study were total of deaths per age group and per municipality in each cause of death calculating the specific rates per inhabitant. Results: The causes of death analized in this paper represent the 77,52 % of the general mortality of the province. For all the studied causes the age group 65 years and more has the hihest mortality rates but particularizing for heart diseases the highest rate belongs to males from Cienfuegos municipality; for malignant tumors to Cumanayagua and Cienfuegos, for Cerebro Vascular Accidents the highest rates are for females from Cienfuegos municipality, influenza and pneumonia has the highest incidence in males from Aguada and suicide attempt in males from Aguada, Cruces and Cienfuegos respectively.